Im Diesseits das Jenseits bereiten Eschatologie, Laienbildung und Zeitkritik bei den mittelniederländischen Autoren Jan van Boendale, Lodewijk van Velthem und Jan van Leeuwen - Wuttke, Ulrike (Universitätsverlag Göttingen, 2016)
This study reveals that in medieval Dutch vernacular texts (from the Brabantine authors Jan van Boendale, Lodewijk van Velthem, and Jan van Leeuwen, and in the anonymous Boek van Sidrac) the treatment of individual and universal eschatological topics and themes, such as death, heaven, hell, purgatory, the Antichrist, eschatological people, and Judgement Day is dedicated to moral and ethical guidance to prepare oneself during lifetime for the afterlife. Central to all texts is the fate of the souls in the afterlife and guidelines to assure redemption on Judgment Day. This includes the ability to recognize the signs of the End properly. The vernacular eschatological discourse is considered as an inherent part of the intellectual emancipation of the laity in the later Middle Ages. This book is of interest not only to Dutch and German philologists, but also to historians and anyone interested in the history of religion, especially of eschatology and apocalypticism. This study was awarded with the 2013 Mgr. C. de Clercqprijs of the Koninklijke Vlaamse Academie van België voor Wetenschappen en Kunsten (Royal Flemish Academy of Belgium for Science and the Arts) for an outstanding work in the field 'History of Religions of Flanders'.